Discrimination at Young Age: Experimental Evidence from Preschool Children - Parampreet Christopher Bindra; Daniela Glätzle-Rützler; Philipp Lergetporer (Center for Economic Studies and ifo Institute (CESifo), 2018)
Discrimination is an ubiquitous phenomenon in many societies, but little is known about its origins in childhood. In a framed field experiment, we let 142 three to six-year old preschool children allocate a fixed endowment between an in-group and an out-group receiver in two domains (gender and group affiliation). Discrimination is prevalent in our subjects, since they allocate more than half of their endowment to the in-group. The extent of discrimination does not differ between domains, suggesting that it is a universal, as opposed to a domain-specific, trait. Analyzing age dynamics, we find that discrimination develops with age.
Keywords: C91; C93; D03; 330; discrimination; children; experiment; fairness